Community response to the provision of alternative water supplies: a focus on chronic kidney disease of unknown aetiology (CKDu) in rural Sri Lanka - Horbulyk, Theodore; Kafle, Kashi; Balasubramanya, Soumya (Informa UK Limited, 2021)
Until recently, households in the most chronic kidney disease-affected rural areas of Sri Lanka used untreated groundwater for drinking and cooking, but, by 2018, that share was only 35%. About 50% of households consume water treated by reverse osmosis; others rely on piped water, water delivery by tanker and rainwater harvesting. Based on a new and representative survey of 1500 households, households’ propensities to treat drinking water and adopt improved water sources are shown to be associated with their perceptions of water safety and trust in the institutions that provide alternatives to untreated well water.